Blood Cell Classification Using CNN - Begum, Afroz; Biradar, Veeresh; Nase, Gururaj (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2022)
White Blood Cells otherwise called leukocytes assumes a significant part in the human body by expanding the resistance by battling against irresistible sicknesses. The order of White Blood Cells, assumes a significant part in identification of an infection in a person. The characterization can likewise help with the recognizable proof of sicknesses like contaminations, sensitivities, weakness, leukemia, malignancy, Acquired Immune Deficiency Syndrome (AIDS), and so forth that are caused because of inconsistencies in the invulnerable framework. This characterization will help the hematologist recognize the sort of White Blood Cells present in human body and discover the main driver of infections. As of now there are a lot of examination going on in this field. Considering an enormous potential in the meaning of characterization of WBCs, we will utilize a profound learning strategy Convolution Neural Networks (CNN) which can arrange the pictures of WBCs into its subtypes to be specific, Neutrophil, Eosinophil, Lymphocyte and Monocyte. In this paper, we will report the consequences of different examinations executed on the Blood Cell Classification and Detection (BCCD) dataset utilizing CNN. How to cite this article: Begum A, Biradar V, Nase G. Blood Cell Classification using CNN. J Adv Res Appl Arti Intel Neural Netw 2021; 5(2): 10-17.